High fidelity, low cost moulage as a valid simulation tool to improve burns education. Issue 4 (June 2016) - Pywell, M.J.; Evgeniou, E.; Highway, K.; Pitt, E.; Estela, C.M.
Highlights: We describe new professional techniques to produce moulage in burns simulation. We assess the fidelity of these moulage techniques in burns simulation. We compare these techniques to current methods used on a burns management course. Fidelity is higher using our new techniques compared to existing methods. Professional techniques using low cost materials can provide high fidelity moulage. Abstract: Simulation allows the opportunity for repeated practice in controlled, safe conditions. Moulage uses materials such as makeup to simulate clinical presentations. Moulage fidelity can be assessed by face validity (realism) and content validity (appropriateness). The aim of this project is to compare the fidelity of professional moulage to non-professional moulage in the context of a burns management course. Four actors were randomly assigned to a professional make-up artist or a course faculty member for moulage preparation such that two actors were in each group. Participants completed the actor-based burn management scenarios and answered a ten-question Likert-scale questionnaire on face and content validity. Mean scores and a linear mixed effects model were used to compare professional and non-professional moulage. Cronbach's alpha assessed internal consistency. Twenty participants experienced three out of four scenarios and at the end of the course completed a total of 60 questionnaires. Professional moulage had higher average ratings for face (4.30 v 3.80; p  = 0.11) and content (4.30 v 4.00; p  = 0.06) validity. Internal consistency of face ( α  = 0.91) and content ( α  = 0.85) validity questions was very good. The fidelity of professionally prepared moulage, as assessed by content validity, was higher than non-professionally prepared moulage. We have shown that using professional techniques and low cost materials we can prepare quality high fidelity moulage simulations.